Dakwah Bil Haal Pondok Pesantren Al-Mutawally Di Desa Bojong Kecamatan Cilimus Kabupaten Kuningan - Asikin, Asikin; Mausul, Asep Ahmad (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2020)
The purpose of this study is to describe the form of da'wah activity of bil haal Al-Mutawally Islamic Boarding School, and to find out the goals, targets and supporting and inhibiting factors carried out fromda'wah activities at bil haal Al-Mutawally Islamic Boarding School in Bojong Village, Cilimus District, Kuningan Regency. This study uses a qualitative method. The data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The data analysis technique used in this study is a qualitative descriptive analysis technique. Meanwhile, the validity of the data was checked using the source triangulation technique. The results of this study indicate that: 1) Al-Mutawally Islamic Boarding School in carrying out its da'wah uses bil-lisan, bil-qolam and bil-haal da'wah, but what is more dominant isda'wah bil-haal such as providing scholarships, giving zakat and compensation for orphans . 2) The supporting factors of theda'wah activities bil-haal carried out by the Al-Mutawally Islamic Boarding School are the charismatic nature of the Al-Mutawally Islamic Boarding School Leaders, so that the community's response to the existence of the Al-Mutawally Islamic Boarding School is quite good. 3) The goals and objectives of the da'wah activities of the Al-Mutawally Islamic Boarding School are to create a quality, spiritual and intellectual condition of the surrounding community as the formation of civil society and build a community of faith and piety to Allah and His Messenger.